A Study Of EFL Reading Media Preference And Its Correlation To Gender, Learning Style And Achievement - Kurniawan, Muhammad; Tanduklangi, Amri; Alberth, Alberth (Halu Oleo University, 2018)
The research was aimed to: 1) examine what students prefer most when reading; printed or digital media; 2) examine whether there is an association between media preference (printed vs. digital) and gender; 3) examine the result modes of reading (printed vs. digital) on reading comprehension; examine the association between media preference and achievement; examine the association of reading media preference and learning styles. The study employed descriptive quantitative approach which used Repeated Measure Design to carry out the study. Total of samples involved in this study were 53 students which is selected through purposive sampling. The study employed three main instruments to obtain the data which is consisted to Reading Comprehension test, Reading Media Preference questionnaire and Learning Style Preference Questionnaire. Result of data analysis has drawn a numerous conclusions. First, most of students more like reading printed media than reading in digital media, but most of students were more often using digital reading media in their daily reading activity. Second, descriptively it was found that most of male more like and more often reading digital reading than female and most of female more like and more often reading digital reading than male. Meanwhile, quantitatively, there was no significant association between media preference and gender (P-Value: 0.334 > Î±: 0.05). Third, there was no significant different of reading comprehension between students who read through printed based reading and digital based reading (P-value: 0.896 > Î±: 0.05). Fourth, there was no an association between media preference and achievement. Chi-Square analysis (P-value: 0.239 > Î±: 0.05) and Ordinal Regression analysis (P-value: 0.808 > Î± 0.05) also showed that statistically there was not significant association between reading media preference and reading achievement. Last, in terms of the association of media preference and learning style, it was found that students with auditory learning style were more like printed reading media for their preference but majority of them were often read digital reading in their reading activity. Respondents with a visual learning style more like printed reading than digital reading and they also were more often read printed reading than digital reading. A kinesthetic learning style respondents were more like printed reading and majority of them also were often read printed than digital reading.